Interpreting the theology of Barth in light of Nietzsche"s dictum "God is dead" - Groenewald, André J. (HTS teologiese studies, 2007)
Karl Barth responded with his theology to Nietzsche’s dictum “God is dead” by stating that God is the living God. God does not need the human race to exist. God reveals God self to humankind whenever God wills. Barth agreed with Nietzsche that the god of the nineteenth century was a “Nicht-Gott”. The article aims to discus Karl Barth’s respons to Nietzsche’s impulse towards the development of a concept of God that would lead to neither atheism nor theism. The article argues that Barth paved the way for talking about God by defining God as the “communicative God”.